ANALISIS YURIDIS TERHADAP RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA RINGAN BERDASARKAN KUHAP DAN PERMA NO. 2 TAHUN 2012 - Suwiryo, Rubiono Gatot; Cornelis, Vieta Imelda; Paramitha, Vallencia Nandya (Gapenas Publisher, 2025)
The settlement of minor criminal cases in Indonesia has been dominated by a formal and bureaucratic retributive approach, which is inefficient and causes dissatisfaction among the parties involved. In response to this situation, the restorative justice approach has emerged as an alternative that focuses more on restoring relationships between perpetrators, victims, and the community. This study aims to analyze the legal application of restorative justice in the settlement of minor criminal offenses based on the Criminal Procedure Code and PERMA No. 2 of 2012, as well as a case study of its implementation in the Mojokerto District Court. This study uses a normative legal method, with a literature study approach through analysis of legislation, court decisions, and relevant scientific literature. The results show that although the Criminal Procedure Code does not explicitly regulate the mechanism of restorative justice, the scope for its application can be found in Article 82 of the Criminal Procedure Code, reinforced by PERMA No. 2 of 2012 and Attorney General Regulation No. 15 of 2020. A case study in Mojokerto City proves that this approach is capable of resolving cases quickly, efficiently, and satisfactorily for all parties, especially in cases of minor assault and petty theft. There are still serious challenges, such as the lack of integrated technical regulations, low understanding among law enforcement officials, and cultural resistance to non-punitive approaches. Therefore, policy reformulation, intensive training, and public education are needed to broaden acceptance of restorative justice. This study confirms that the restorative justice approach is not only normatively relevant but also proven to be practically effective in realizing a more just, humane, and sustainable criminal justice system